2018
DOI: 10.1186/s12985-018-1104-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Zika virus envelope protein production for ELISA and correlation of antibody titers with virus neutralization in Mexican patients from an arbovirus endemic region

Abstract: BackgroundZika virus (ZIKV) has become a global threat with immediate need for accurate diagnostics, efficacious vaccines and therapeutics. Several ZIKV envelope (Env)-based vaccines have been developed recently. However, many commercially available ZIKV Env are based on the African lineage and produced in insect cells. Here, we sought to produce Asian-lineage ZIKV Env in mammalian cells for research and clinical applications.MethodsWe designed various gene expression constructs to optimize the production of Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…To test the expression of ZIKV antigens, BHK-21 cells were transfected with rMVA. At 24 h after transfection, BHK-21 cell extracts were tested by Western blot as previously described [19]. Briefly, samples added to Laemmli sample buffer containing 20 mM β-mercaptoethanol, boiled for 5 min, and loaded on a Mini-PROTEAN TGX protein gel with Bio-Rad, Precision Plus Protein TM WesternC TM standards.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To test the expression of ZIKV antigens, BHK-21 cells were transfected with rMVA. At 24 h after transfection, BHK-21 cell extracts were tested by Western blot as previously described [19]. Briefly, samples added to Laemmli sample buffer containing 20 mM β-mercaptoethanol, boiled for 5 min, and loaded on a Mini-PROTEAN TGX protein gel with Bio-Rad, Precision Plus Protein TM WesternC TM standards.…”
Section: Methodsmentioning
confidence: 99%
“…Enzyme-linked immunosorbent assay (ELISA)-recombinant ZIKV Envelope protein was used to measure anti-ZIKV envelope antibody concentrations in vaccinated mice by ELISA as previously described [19]. Briefly, Nunc Maxisorp Immuno ELISA plates were coated with Zika virus envelope antigen (Env-CD4) diluted in PBS to a final concentration of 2 µg/mL and left at room temperature (RT )overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For ELISA in BALB/c mice before challenge, antibody endpoint titres are the highest reciprocal serum dilution that resulted in an absorbance >2-fold over the background values, as calculate elsewhere [36]. Anti-Zika envelope antibody concentrations in A129 mice sera before challenge was measured by IgG ELISA using Zika Env antigen as previously described [48].…”
Section: Enzyme-linked Immunosorbent Assay (Elisa) To Quantify Whole Iggmentioning
confidence: 99%
“…Interestingly, three of the vaccine candidates provided 100% protection: the Asian-lineage based vaccines ChAdOx1 prME and ChAdOx1 prME ∆ TM, as well as the African-lineage based vaccine ChAdOx1 CprME/NS. We sought to analyse the levels of anti-ZIKV envelope antibodies at 1 dbc by using ELISA plates coated ZIKV AS envelope 23 (Figure 3b). Sera from control groups were negative and Log10 reciprocal titers showed that all ChAdOx1 ZIKV vaccines elicited anti-envelope responses.…”
Section: Mainmentioning
confidence: 99%